The Influence Of Job Stress, Job Motivation and Job Satisfaction On Employee Performance At Pt Pancaran Sinar Rajawali Indonesia - Abdul Fatah (Universitas 17 Agustus 1945, 2021)
The aim of this research is to examine the influence of work stress, work motivation and job satisfaction on employee performance at PT Pancaran Sinar Rajawali Indonesia, both simultaneously and partially. This research uses an explanatory quantitative approach. The number of samples in this study was 35 respondents The results of this research in hypothesis 1 obtained the results of t count > t table (2.362 > 1.989) with a significance level of 0.02 (0.02 < 0.05) Hypothesis 2 obtained the results of t count > t table (2.398 > 1.989) with a level of significance of 0.02 (0.02 < 0.05). Hypothesis 3 obtained the results of t count > t table (2.659 > 1.989) with a significance level of 0.01 (0.01 < 0.05). Hypothesis 4 obtained the results of F count > F table (7.566 > 2.717) with a significance level of 0.00 (0.00 < 0.05) which means there is a significant influence between work stress, work motivation and job satisfaction on employee performance. The conclusion of this research is that in hypotheses 1 to hypothesis 4 there is a significant influence on work stress, work motivation and job satisfaction on the performance of PT Pancaran Sinar Rajawali Indonesia employees.